Bacteria-Killing Type IV Secretion Systems - Sgro, Germán G.; Oka, Gabriel U.; Souza, Diorge P.; Cenens, William; Bayer-Santos, Ethel; Matsuyama, Bruno Y.; Bueno, Natalia F.; dos Santos, Thiago Rodrigo; Alvarez-Martinez, Cristina E.; Salinas, Roberto K.; Farah, Chuck S. (Frontiers in Microbiology, 2019)
Bacteria have been constantly competing for nutrients and space for billions of years. During this time, they have evolved many different molecular mechanisms by which to secrete proteinaceous effectors in order to manipulate and often kill rival bacterial and eukaryotic cells. These processes often employ large multimeric transmembrane nanomachines that have been classified as type I to IX secretion systems. One of the most evolutionarily versatile are the Type IV secretion systems (T4SSs), which have been shown to be able to secrete macromolecules directly into both eukaryotic and prokaryotic cells. Until recently, examples of T4SS-mediated macromolecule transfer from one bacterium to another was restricted to protein-DNA complexes during bacterial conjugation. This view changed when it was shown by our group that many Xanthomonas species carry a T4SS that is specialized to transfer toxic bacterial effectors into rival bacterial cells, resulting in cell death. This review will focus on this special subtype of T4SS by describing its distinguishing features, similar systems in other proteobacterial genomes, and the nature of the effectors secreted by these systems and their cognate inhibitors.